Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Hasil Belajar siswa KelasXI pada Mata Pelajaran Teknik Frais di SMK Negeri 1 Tanjung Raya - Ibnu Abid Al Rasyid; Abdul Aziz; Purwantono Purwantono; Eko Indrawan (Jurusan Teknik Mesin Fakultas Teknik Unversitas Negeri Padang, 2020)
The educational model applied by teachers to the frais method subjects at State 1 Tanjung Raya Vocational High School (SMK) is not quite right. The purpose of this research is to increase student learning outcomes in the Milling Method subject by using a Project Based Learning based education model that is appropriate and instantaneously applied in Vocational High Schools (SMK) Negara 1 Tanjung Raya. The procedure for this research is classroom action research which is often called classroom action research. This research was carried out using 2 cycles, the second cycle was carried out if cycle 1 the results were not satisfactory. Until the application of cycle 2 is continued, if the results are not satisfactory, then the researcher may carry out the next cycle, the researcher may stop when the results are satisfactory. The results of this research on the application of cycle I in education using a project-based education model, the average student score increased from 76.3 to 79.7. The number of students who faced an increase in grades was 14 people. with a classical completeness percentage of 53, 84%. In the application of cycle 2 the average score of students increased from 79.7 to 85.5. The percentage of classical learning completeness increased from 53.84% to 88.46%. After carrying out research by conducting 2 cycles until a conclusion is obtained from the results of classroom action research, it can be recognized that the Implementation of Project-Based Education Procedures in the Milling Method Subject can improve student learning outcomes, as well as raise students' confidence in doing work.